Post-pandemic tourism: The desired wave of recovery in India - Saxena, Sanjeev Kumar; Kumar, Ashish; Kumar, Pankaj (Turyzm/Tourism, 2021)
In post-pandemic India the recovery in tourism has become known as ‘revenge’ meaning revenge on the disease. It is tourism due to the desperation to travel, especially in the current scenario in which those who have been confined to their homes have grown tired of being trapped there. The restless mood caused by the ongoing pandemic reached its peak and it is possible that this will eventually help in bringing back a rapid return to tourism. To analyze the travel intentions of potential tourists after the current pandemic ends, an attempt has been made to make an analysis of tourism in India to find out how Covid-19 is impacting on people’s lives and how willing they are to participate in tourism again.